Developing media literacy in cyberspace : pedagogy and critical learning for the twenty-first- century classroom - Frechette, Julie D., 1971- (Praeger, 2002)
In this age of electronic information overload, argues Frechette (communications, Worchester State College), the Internet-supported classroom must incorporate media literacy in order to help students become critical citizens. Rather than having online information blocked or filtered from them, she s.